Re-Inventing the Past, Defining the Future: Historical Representations and Regional Development in the Russian Northwest - Sorokina, Alfia (Université d'Ottawa / University of Ottawa, 2010)
This work explores the connections between the constructed representations of places based on local histories, the processes of tradition reinvention and the strategies of regional development in two Russian regions. This analysis also outlines the context created by the external to the regions influences and the associated with them local conditions.
Keywords: social field of historical production; territorial identity and development; re-invented traditions; owning development; regional image; historical representations; development resource pool; regional development; local development